2012
DOI: 10.1152/ajpcell.00180.2011
|View full text |Cite
|
Sign up to set email alerts
|

l-Mimosine blocks cell proliferation via upregulation of B-cell translocation gene 2 and N-myc downstream regulated gene 1 in prostate carcinoma cells

Abstract: L-Mimosine, an iron chelator and a prolyl 4-hydroxylase inhibitor, blocks many cancer cells at the late G1 phase. B-cell translocation gene 2 (Btg2) regulates the G1/S transition phases of the cell cycle. N-myc downstream regulated gene 1 (Ndrg1) is a differentiation-inducing gene upregulated by hypoxia. We evaluated the molecular mechanisms of L-mimosine on cell cycle modulation in PC-3 and LNCaP prostate carcinoma cells. The effect of L-mimosine on cell proliferation of prostate carcinoma cells was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…Induction of TGFβ1 signaling was monitored by immunodetection of phosphorylated SMAD2 (pSMAD2). As expected, L-mimosine and TGFβ1 treatment decreased the levels of cyclin A2 (CCNA2) indicating cell cycle arrest [15,20,21]. Hmga2 transfection minimally reduced CCNA2 levels.…”
Section: Tgfβ1-induced Transcription Requires Hmga2 Atm and H2axs139phsupporting
confidence: 66%
See 1 more Smart Citation
“…Induction of TGFβ1 signaling was monitored by immunodetection of phosphorylated SMAD2 (pSMAD2). As expected, L-mimosine and TGFβ1 treatment decreased the levels of cyclin A2 (CCNA2) indicating cell cycle arrest [15,20,21]. Hmga2 transfection minimally reduced CCNA2 levels.…”
Section: Tgfβ1-induced Transcription Requires Hmga2 Atm and H2axs139phsupporting
confidence: 66%
“…In addition, several reports suggest an increase of H2AX-S139ph during cell cycle progression due to DNA replication stress [18,19]. Thus, to discriminate between transcription-related H2AXS139ph and DNA replication stress-induced H2AXS139ph, we used L-mimosine, a cell cycle inhibitor that is known to increase DNA replication stress [20,21]. Protein extracts of MLE-12 cells that were either transfected with Hmga2 or treated with L-mimosine or TGFβ1 were analyzed by WB (Supplementary information, Figure S3C).…”
Section: Tgfβ1-induced Transcription Requires Hmga2 Atm and H2axs139phmentioning
confidence: 99%
“…A range of prostate cancer specimens analysed by immunohistochemistry have shown that NDRG1 expression is lower in neoplastic when compared with adjacent normal tissues 19. This finding was further substantiated by the discovery of an inverse relationship between the Gleason grade of the cancer with NDRG1 expression levels, where a higher grade corresponds to poorly differentiated tumours with low NDRG1 protein expression 58 59. This finding is also observed in colon cancer where the expression of NDRG1 declines as normal colonic epithelium progresses to carcinoma 60.…”
Section: Role Of Ndrg1 In Primary Tumour Growth Metastasis and Angiomentioning
confidence: 83%
“…Future studies would confirm BTG2 as a prognostic marker for HCC patients, and further investigate the usefulness of BTG2 as a therapeutic target for HCC patients. BTG2 is a member of the anti-proliferative family of proteins (25), and plays an essential role in regulating cell proliferation, apoptosis and DNA repair (13,26,27). Several previous studies have reported that BTG2 expression was reduced in various human cancers including renal cell carcinoma, prostate cancer, gastric cancer, melanoma, breast cancer and lung cancer (8,(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%